Leading Causes of Mortality from Diseases and Injury in Nepal: A Report from National Census Sample Survey - Sharma, G.K. (Journal of Institute of Medicine Nepal, 2007)
Background: The burden of injuries in relation to other diseases has been inadequately addressed in most of the official publications and scientific literature relating to Nepal. Objectives: In the current constraint of poor availability of such information, National Census Sample Survey information was utilized to understand the mortality pattern of major forms of injuries in relation to all diseases. Methods: A nationally representative sample was drawn from six districts and 52 municipalities as a part of national census sample survey. The instrument included respondent-reported deaths in the family, the cause of death, the age and sex. Results: The national representative information on the pattern of diseases shows that there were 7,010 deaths as a result of the external causes of injuries (4,803 males and 2,207 females) in a period of one year prior to the survey in 2001. Suicides, transport related accidents and other accidents accounted for the largest proportion of injuries. Other accidents ranked sixth, suicide 9th and transport accidents 10th leading cause of death for both sexes and all diseases. Conclusion: Injuries accounted for as many number of death as tuberculosis and many times more than malaria or HIV/AIDS in Nepal. External causes of injuries are therefore a major burden of mortality and morbidity in an impoverished country like Nepal and needs an urgent public health attention. Journal of Institute of Medicine Vol.28(1) 2006